Gradient-Regeneration of Li(Ni0.9Co0.05Mn0.05)O2 from Spent LiCoO2 lithium-Ion Battery. Issue 16 (4th January 2021) - Wang, Guange; Wu, Tong; Liu, Borui; Gong, Shanshan; Huang, Qing; Su, Yuefeng; Wu, Feng; Kelly, Ryan M.
Abstract : Considering that lithium-ion battery (LIB) is still an indispensable and important component of energy storage materials, the sustainable post-processing of spent LIBs in labs or enterprises becomes a tricky problem. Herein, a novel scheme is proposed to dissert the recycling of the spent LIBs. The LIB is recycled into Li(Ni0.9 Co0.05 Mn0.05 )O2 (NCM90) cathode material with high specific capacity by introducing an innovative hydrometallurgy-coprecipitation treatment method. The spent LiCoO2 (LCO) cathode material is firstly leached by sulfuric acid, and the leachate is gradient used as the raw materials to resynthesize high-nickel NCM material by adjusting the leachate dosage to about 50%. Interestingly, when the dosage exceeds 50%, the crystal structure aggravates, and Li + /Ni 2+ mixing improves. The specific capacity of regenerated battery is 181.4 mAh g −1 at 0.5 C (1 C = 200 mAh g −1 ) and the capacity retention achieves 93.2% after 100 cycles. The reasons can be attributed to the cation mixing and crystal strucure and the small amount of Al doping. In conclusion, this combined method recycling of LIBs has huge potential value for environment protection and production.